THE UTILIZATION OF RED MEAT WASTE IN THE MAKING OF CRACKERS - Inang Musa; Sunarto Kadir; Arpin (Journal of Health, Technology and Science (JHTS), 2021)
Red Tuna Fish waste contains vitamin B6 which functions to increase hemoglobin production, maintain brain cell function, and help the body produce serotonin and norepineprine hormones. The formulation of the problem in this study is what is the right composition for making tuna red meat crackers. How is the community's acceptance of the quality of the addition of tuna red meat crackers. The research objectives were to determine the exact composition of tuna red meat crackers and to determine the public acceptance of the quality of crackers with the addition of tuna red meat waste based on color, taste, aroma and texture. This research uses analytic observational research where the research is conducted by analyzing acceptance. The population used was 352 people in Bilato Village, Bilato District and a sample of 176 respondents. Data collection techniques using hedonic questionnaires with data analysis techniques using qualitative descriptive analysis. The results showed that the crackers preferred by the panelists were 100 gr and 200 gr with very like criteria but the most preferred by the panelists were 100 gr crackers with very like criteria, 50 gr crackers were less preferred by the panelists with moderate criteria. Suggestions from research for campus institutions as references and information for further research, for students to further modify the food material for tuna red meat waste so that it can be used as the latest research material and see the RDA contained in fish waste red meattuna